Synthesis, characterization and application of amine-modified Macadamia nutshell adsorbents and ion imprinted polymers for the sequestration of Cr(VI) ions from aqueous solution - Nchoe, Obakeng Boikanyo (My University, 2018)
Persisting challenges associated with remediation of heavy metals from aqueous media have stirred the need for enhancement of current technologies. Cellulosic agro waste materials (AWM) as well as ion-imprinted polymers (IIP) have received ardent attention from researchers. These materials are often employed in the following industries: water and wastewater treatment, medical, pharmaceutical and packaging. Applications in water and wastewater treatment have gained significant interest due to desirable features they possess. In the case of AWM, these features include a tuneable surface area and poor porosity, basic surface functional groups and chemical stability. Some desired features in IIP include adsorption sites compatible for the ion imprint obtained after leaching with suitable reagents, rigidity and reusability. The efficacy of employing AWM and IIP for the remediation of toxic chromium from aqueous solution was explored. The current study is made up of part A and B. In part A, Macadamia nutshell powder was treated using HNO3, NaOH, as well as Fenton’s reagent. The three materials underwent a new modification which involved reacting treated adsorbents with cetyltrimethylammonium chloride (CTAC), followed by immobilization of 1,5' diphenylcarbazide (DPC) ligand. The adsorbents were ultimately washed, dried and stored for Cr(VI) batch adsorption experiments. Part B involved a synthesis of IIP and their non-imprinted polymer counterpart (NIP) for Cr(VI) sequestration in aqueous solution. This was done by precipitation polymerization of functional monomers, crosslinker and DPC-Cr(VI) complex as a template. Non-imprinted polymers were fashioned in a manner like that of IIP but with the exclusion of Cr(VI) ion template. Characterizations of the adsorbents were done using Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), X-ray fluorescence (XRF), and carbon, hydrogen, nitrogen and sulphur (CHNS) analyzer. Batch adsorption experiments were done and parameters such as solution pH, adsorbent dosage, initial Cr(VI) concentration and contact time were optimized. Working solutions were analyzed using ultraviolet-visible (UV-Vis) and atomic absorption (AA) spectroscopy. Adsorption parameters found to be optimum for DPC immobilized cellulosic adsorbents were pH 1.4, adsorbent mass of 0.1 g, 100 mg/L initial concentration and 125 minutes of contact time. The adsorption parameters determined to be optimum for IIP and NIP were pH 2.6, 0.2 g adsorbent mass, 80 mg/L initial concentration and 240 minutes of contact time. Reusability studies demonstrated the potential of adsorbents to remove Cr(VI) ions from aqueous media after successive adsorption-desorption cycles. Selectivity studies indicated that DPC immobilized adsorbents as well as IIP were able to selectively adsorb Cr(VI) ions from aqueous media in the presence of Zn(II), Cu(II), Co(II) and NI(II) ions. Kinetic models revealed that DPC immobilized cellulosic adsorbents and synthetic IIP were most fitting for pseudo-second order and pseudo first order, respectively. On the other hand, adsorption isotherm studies demonstrated that DPC immobilized cellulosic adsorbents and synthetic polymers were best fit for Freundlich and Langmuir adsorption isotherm, respectively.
M. Tech (Department of Chemistry, Faculty of Applied and Computer Sciences) Vaal University of Technology.
Keywords: Atomic absorption, aqueous media, adsorbent mass, adsorption-desorption, thermogravimetric analysis (TGA); Polymerization.; Macadamia nut.; Carbon sequestration.